Ruxolitinib Associated Tuberculosis Presenting as a Neck Lump - Eamon Shamil; David Cunningham; Billy L. K. Wong; Piyush Jani (Case Reports in Infectious Diseases)
Tuberculosis is an opportunistic infection with protean clinical manifestations. We describe a case of Ruxolitinib induced miliary tuberculosis presenting as a neck lump. A 78-year-old female presented with a two-month history of right-sided neck lump associated with fever, night sweats, and significant weight loss. She had a past medical history that included myelofibrosis, being treated with Ruxolitinib. Examination demonstrated 4 × 4 cm right-sided cervical lymphadenopathy. A chest radiograph showed extensive shadowing in both lungs. CT scan demonstrated perilymphatic nodes in addition to the cervical mass. An ultrasound-guided biopsy of a cervical lymph node demonstrated confirmed Mycobacterium tuberculosis infection. It was hypothesized that use of Ruxolitinib through its selective inhibition of Janus-activated kinases 1 and 2 resulted in immunosuppression and miliary tuberculosis in this patient. The medication was stopped and a 12-month regime of antituberculosis therapy commenced. She remained well at one-year follow-up with resolution of lung involvement. Clinicians should consider tuberculosis as a differential diagnosis for patients presenting with a neck lump, particularly in those taking immunosuppressant medication such as Ruxolitinib. A multidisciplinary approach is needed to promptly treat the tuberculosis and consider discontinuation of Ruxolitinib.